Workshop Penelitian Tindakan Kelas (PTK) di SMP Dwijendra Bualu untuk Meningkatkan Pemahaman PTK Guru - I Putu Ade Andre Payadnya; I Made Dharma Atmaja; I Putu Dimas Sedana Arta; Ida Bagus Krisna Indira Putra; Azura Ningrum Septi Utami (Randang Tana - Jurnal Pengabdian Masyarakat, 2024)
The purpose of this community service activity is to increase Dwijendra Bualu Middle School teachers' understanding of the significance and methodology of Classroom Action Research (CAR). The place for this activity was at Dwijendra Bualui Middle School, located in Nusa Dua, Bali. The participants in this activity were 12 Dwijendra Bualu Middle School teachers. The time for implementing this PKM activity is in the Even Semester of the 2022/2023 Academic Year. The implementation methods can be seen in the Significance of PTK Workshop and the Methodology of PTK Workshop. The stages of implementing this community service activity include: the planning stage, the preparation stage, the implementation stage, and the evaluation stage. This community service method includes CAR significance workshops and CAR methodology workshops. The results obtained were a very good increase in the level of teachers' understanding of PTK through the results of the pre-test and post-test, namely by 94% Positive responses were also shown by teachers who found the material presented useful and motivated them to do CAR.